Estratégias de leitura para alunos com TDAH: um estudo de caso - Favero, Suelen (2022)
From mental origin, Attention Deficit Hyperactivity Disorder presents characteristics of a persistent pattern of inattention and/or hyperactivity and impulsivity. According to the literature, it is a risk factor for poor school performance and can hinder the development of reader comprehension. With regard to the development of reader comprehension, Isabel Solé (1998) presents a reading plan to be carried out, during and after the act of reading. In this sense, it presents the investigation sought to investigate how the reading strategies by this author can contribute to the understanding of students with ADHD. More specifically, it is intended to: (a) Discuss Attention Deficit Hyperactivity Disorder and the reading strategies recommended by Solé (1998); (b) identify related studies in the specialized literature; (c) develop and implement a didactic proposal structured according to the author's conceptions; and (d) analyzed how these types of strategies can help in the development of definition, understanding and inter pretation of texts by students with the isorder. For this purpose, a qualitative study was carried out and type “case study of case”, based on the proposal of Trivinõs (1987), with a student with ADHD. They were obtained through an important intervention to the participant, which were the texts used, the records contained after the researcher's logbook and the videos with long data from the meetings. Data analysis was based on Bardin's Content Analysis charts (2016) and as categories of analysis, defined a priori, were called Decoding, Understanding and Interpretation. The results obtained indicate that they organize reading activities according to the proposals proposed by Solé (1998), which favored and potentiated the development of definition, understanding and interpretation of texts by students with Attention Deficit Hyperactivity Disorder.